Monitoring of benzene, toluene, ethyl benzene, and xylene isomers emission from Shahreza gas stations in 2013 - Farhad Esmaelnejad; Yaghoub Hajizadeh; Hamidreza Pourzamani; Mohamad Mehdi Amin (International Journal of Environmental Health Engineering, 2015)
Aims: The aims of this study were to monitor the concentration of benzene, toluene, ethyl benzene and xylenes (BTEX) in the ambient air of the city of Shahreza gas stations and to identify the spreading distance of the pollutants from the fueling stations. Materials and Methods: Sampling was carried out from the air of 10 existing fuel stations, (2 compressed natural gas and 8 gasoline and diesel stations) and points of 50, 150 and 250 m away from the stations during cold and warm seasons in 2013. Air samples were taken via active sampling process using activated carbon tubes, extracted by carbon disulfide and analyzed by a gas chromatograph coupled to a flame ionization detector. Results: The averages of all achieved BTEX concentrations were under/around the permitted guideline levels for occupational exposure. According to the ambient air guidelines, the benzene level was much higher than the suggested levels in all the stations. However, the average concentrations of toluene, ethyl benzene, and xylene were not exceeded from the standards. The seasonal variation had no influence on the concentrations of BTEX. There was no significant difference between the pollutants concentrations at points 50, 150 and 250 m away from the stations. Conclusions: Fuel stations could be the main sources of volatile organic compounds emission in the city of Shahreza. The number and volume of refueling in the gas stations influence the emission rates. Therefore, it is suggested to take preventive actions such as repairing of pumps and tanks leak and installing vapor return systems at the time of fuel transferring.